2020
DOI: 10.1364/ol.406280
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the 2D limit: étendue-squeezing line-focus solar concentrators

Abstract: Line-focus solar concentrators are commonly designed by extruding a two-dimensional concentrator in the third dimension. For concentration in air, these concentrators are, by the nature of their design, limited by the two-dimensional solar concentration limit of . This limit is orders of magnitude lower than the concentration limit for three-dimensional solar concentrators. Through the use of étendue squeezing, we conceptually show that it is possible to design line-focus solar concentrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…Concentrations ranging from 1-100× are considered, as well as temperatures up to 225 • C. Each of these ranges corresponds to the performance of a class of deployed or proposed line-focus solar concentrators. "Etendue-squeezing" concentrators with dual-axis tracking have been proposed for thermal and chemical applications that can reach 100× concentration factors with a 1-degree acceptance angle [57]; 200-250 • C is the upper limit of the performance of low-concentration compound parabolic collector (CPC) modules that are currently in commercial production [58]. While this temperature range is seen as too high for PV cell operation, this is not necessarily the case as can be seen from the figure.…”
Section: Pv-thermal Applicationsmentioning
confidence: 99%
“…Concentrations ranging from 1-100× are considered, as well as temperatures up to 225 • C. Each of these ranges corresponds to the performance of a class of deployed or proposed line-focus solar concentrators. "Etendue-squeezing" concentrators with dual-axis tracking have been proposed for thermal and chemical applications that can reach 100× concentration factors with a 1-degree acceptance angle [57]; 200-250 • C is the upper limit of the performance of low-concentration compound parabolic collector (CPC) modules that are currently in commercial production [58]. While this temperature range is seen as too high for PV cell operation, this is not necessarily the case as can be seen from the figure.…”
Section: Pv-thermal Applicationsmentioning
confidence: 99%
“…[3][4][5][6] In previous research, we have demonstrated that one way to perform this symmetry-breaking is through étendue squeezing. 7,8 An alternate and lesser known principle for breaking the continuous translational symmetry of an optical system is étendue rotation. 9 Here, we show through two different configurations how this principle can be used to increase the concentration of line-focus solar concentrators beyond the 2D concentration limit.…”
Section: Introductionmentioning
confidence: 99%